Sustainable Development as a Macro-Regional Goal - Porrini, Donatella; Striani, Fabrizio (Journal of Reviews on Global Economics, 2017)
The idea of sustainable development emerged both from science and the environmental movement in the 70s and 80s of last century. Since then a lot was done in the field, sometimes without even naming it "sustainable development", but a lot still remains to be done. In this paper we start from the consideration that sustainable development requires that we see our world as a system that connects space and any discussion today must first consider the enormous impacts that modern globalization trends are playing in shaping the economic geography of places, such as macro-regions. In the future, macro-regional development could be the most important platform for enhancing sustainability. The regional dimension is suitable for redefining the meaning of sustainable social, economic and environmental systems in a way which is practical and very close to the people and to the operative public decisions (Alkan Olsson et al. 2004). This paper is divided in different sections: the first is about the regional sustainable development concept and place-based approach; the second is about Local Agenda 21; the third about regional integration and developmental regionalism; the fourth is about regional sustainable development in practise and the European macro-regions; at the end some conclusive remarks concerns the macro-regional future strategies addressing sustainable development.